Effect of standardized root extract of ashwagandha (Withania somnifera) on well‐being and sexual performance in adult males: A randomized controlled trial - Sanjaya Chauhan; Manoj K. Srivastava; Anklesh K. Pathak (Health Science Reports, 2022)
Abstract Background and Aim In Ayurveda, ashwagandha is a popular plant for promoting youthful energy, longevity, and overall well‐being. It is also an excellent aphrodisiac herb that aids in the improvement and maintenance of normal sexual health. The present study aims to evaluate the effect of ashwagandha root extract on improving sexual health in adult males. Methods In this 8‐week randomized, double‐blind, placebo‐controlled study, we investigated the aphrodisiac property of an ashwagandha root extract in adult males. Fifty participants with lower sexual desire were randomly allocated to take 300 mg of ashwagandha root extract or placebo capsules twice daily. Outcomes were measured using the derogatis interview for sexual functioning‐male (DISF‐M) questionnaire, serum testosterone, serum prolactin, and short‐form survey—36 quality of life questionnaire before and after the intervention. Results Compared to placebo, ashwagandha root extract supplementation was associated with a statistically significant increase in the total DISF‐M scores (mean difference −9.8; 95% confidence interval, −10.73 to −8.87; p < 0.0001; t‐test). It was also associated with a statistically significant increase in serum testosterone levels (−66.52; −80.70 to −52.34; p < 0.0001; t‐test). However, the prolactin level did not change after intervention in both the ashwagandha and placebo groups (−1.06; −2.78 to 0.66; p > 0.05). Conclusion These findings suggest that ashwagandha demonstrated a significant subjective perception of sexual well‐being and assisted in increasing serum testosterone levels in the participants.